The Correlation Between Metakognitive Skill and Cognitive Learning Result of Students in Scientific Learnings in the Subject Biology High School Curriculum 2013 - Ninik Kristiani (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Metacognitive skills is seen as one of the factors that influence the cognitive learning. Relations metacognitive skills and cognitive learning outcomes can be achieved through the use of specific instructional strategies. Thus the relationship has been much studied. However, the study of the relationship of metacognitive skills and cognitive learning outcomes in learning biology curriculum implemented in 2013 is still lacking. This study is a correlational study revealing the relationship metacognitive skills of students with cognitive learning outcomes on the use of scientific learning strategies. The study was conducted during the semester. The study population was class X SMA Negeri 1 Malang, Indonesia. Samples taken as a single class taught using scientific learning strategy which is often known as 5M. The results show that there is a relationship metacognitive skills of students with cognitive learning outcomes in the application of scientific learning. The regression equation based on the results of the data analysis is y = 0,493x + 20.37 with the reliability value of  0.549  which means donations metacognitive skills of students on the cognitive learning is 54.9%, while 45.1% are other factors besides metacognitive skills. Conclusions based on these results that the students' metacognitive skills associated with cognitive achievement on the use of scientific learning.Keywords: metacognitive skills, the cognitive learning, learning scientific